Analysis of material costs in the production cost ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the specifics of material costs within product cost and their impact on production efficiency. Based on two-year enterprise data, it analyzes the dynamics of material expenses and applies factor decomposition to assess changes in material intensity through key parameters such as the share of material costs and unit costs. The study highlights the practical importance of identifying factors that increase material intensity and finding reserves to reduce costs.
Keywords: material costs; production cost; economic analysis